Analysis on Thermodynamic Perfectibility of Room Air Conditioners - Li Xiaofeng; Ma Yitai; Yan Qiuhui (Zhileng xuebao)
According to analysis on the energy efficiency standards of the constant speed room air conditioner and the variable speed type, differences between the two kinds of air conditioners exist in division standard, grades of energy efficiency and outdoor temperature starting refrigeration. Therefore, a survey was made about cooling capacity and EER as well as energy efficiency grades of the constant and variable speed room air conditioners. The thermodynamic perfectibility of the two types of room air conditioners was calculated for the performance evaluation. The calculation results show that energy efficiency standard of variable speed room air conditioners in 2008 is lower than that of constant room air conditioners. A new energy efficiency standard of the variable speed air conditioner is suggested in accordance with the consistent thermodynamic perfectibility.